The Figure of the Fox in Leanne O'Sullivan's A Quarter of an Hour - David Nisters (Review of Irish Studies in Europe)
The poems that make up Leanne O’Sullivan’s collection A Quarter of an Hour conceptualise the sickness, coma and eventual recovery of her husband, Andrew, in terms of his journey through an ‘inflamed world’. Among the characters who offer guidance to Andrew on this journey, the figure of the fox takes on a particularly prominent role both on account of the frequency of its appearance throughout the collection and because she represents the ambiguous nature of Andrew’s coma as a liminal state that is situated ‘betwixt and between’ life and death. As an agent that is at once dangerous and supportive, the figure of the fox thus embodies a paradoxical condition, functioning as a signifier that brings together contradictory notions, most importantly the loss and retrieval of Andrew’s memory. With regard to her liminal role in Andrew’s journey from sickness to recovery, moreover, the animal crucially resembles the fox of the medieval bestiary tradition. Epitomised by its portrayal in such works as Isidore of Seville’s Etymologies or the Middle English Physiologus, the fox of the bestiary is, in fact, predominantly characterised as shifty, cunning and dangerous. Still, bestiaries also fulfilled an important mnemonic function in medieval textual cultures. Just like Andrew’s fox, therefore, the fox of the bestiary can be characterised as an ambiguous figure that is at once helpful and detrimental, thus providing an important historical frame of reference for considering the conceptualisation of Andrew’s sickness, coma and recovery in A Quarter of an Hour.